2000
DOI: 10.2307/3871209
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in CER6, a Gene Identical to CUT1, Differentially Affect Long-Chain Lipid Content on the Surface of Pollen and Stems

Abstract: Very long chain lipids contribute to the hydrophobic cuticle on the surface of all land plants and are an essential component of the extracellular pollen coat in the Brassicaceae. Mutations in Arabidopsis CER genes eliminate very long chain lipids from the cuticle surface and, in some cases, from the pollen coat. In Arabidopsis, the loss of pollen coat lipids can disrupt interactions with the stigma, inhibiting pollen hydration and causing sterility. We have positionally cloned CER6 and demonstrate that a wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(142 citation statements)
references
References 17 publications
8
132
2
Order By: Relevance
“…The cut1 phenotype involves sense suppression; these plants completely lack epicuticular waxes on stems and siliques and are conditionally male-sterile because of the lack of VLCFAs in the extracellular pollen coat (14). Keeping in mind that the CUT1 amino acid sequence is very similar to that of CER60, sense-suppression plants are possibly deficient in mRNAs for both genes, resulting in a stronger phenotype (34). These dysfunctions and their phytotoxic consequences show the broad spectrum of possible herbicide action caused by VLCFAE inhibition, exemplified by plants that, when treated with low concentrations of flufenacet, produce a phenocopy of the fiddlehead mutant organ-fusion phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The cut1 phenotype involves sense suppression; these plants completely lack epicuticular waxes on stems and siliques and are conditionally male-sterile because of the lack of VLCFAs in the extracellular pollen coat (14). Keeping in mind that the CUT1 amino acid sequence is very similar to that of CER60, sense-suppression plants are possibly deficient in mRNAs for both genes, resulting in a stronger phenotype (34). These dysfunctions and their phytotoxic consequences show the broad spectrum of possible herbicide action caused by VLCFAE inhibition, exemplified by plants that, when treated with low concentrations of flufenacet, produce a phenocopy of the fiddlehead mutant organ-fusion phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…4). Probes were generated from a set of genes known to be implicated in epidermal wax biosynthesis: CUT1͞CER6 (11,17), KCS1 (10), CER1 (16), CER2 (24,26), CER3 (25), and FDH (20,21). Among these genes, CER1 presented the most striking change in gene expression: its transcript level was clearly correlated with the strength of WIN1 overexpression.…”
Section: Genes Encoding Cognate Wax Biosynthetic Enzymes Are Induced Inmentioning
confidence: 99%
“…To date, 11 genes have been identified that are involved in wax biosynthesis or its regulation in plants. Seven of these genes, CER1, CUT1͞CER6, KCS1, WAX2, and FIDDLEHEAD (FDH; all from Arabidopsis), GLOSSY1 (GL1), and GLOSSY8 (GL8; from maize), are predicted to encode enzymes or components of the secretory pathway (10,11,(16)(17)(18)(19)(20)(21)(22). Another four encode regulatory proteins or proteins thought to play a regulatory role: GL2, GL15, CER2, and CER3 (23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…CER6 was required for elongation of C24 VLCFAs (Millar et al 1999) and cer6 plants were glossy and sterile due to lower wax load on cuticle of their stems and pollens (Fiebig et al 2000). Wax-deWcient mutants of maize (Zea mays) also exhibited similar glossy phenotype (Tacke et al 1995;Moose and Sisco 1996;Hansen et al 1997;Xu et al 1997), and rice (Oryza sativa L.) wda1 mutant was sterile because of speciWc wax deWciency on anthers (Jung et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the plant cuticle is essential in precluding postgenital organ fusions (Lolle et al 1992) and in mediating pollen-stigma interactions (Fiebig et al 2000). In rice, the cereal model species, cuticular wax composition was found early to be closely related to resistance to water diVusion, rice blast infection, and brown planthopper damage (O'Toole et al 1979;Kumar and Sridhar 1987;Woodhead and Padgham 1988).…”
Section: Introductionmentioning
confidence: 98%